KARAKTERISTIK DEMOGRAFI IBU DENGAN KEMAMPUAN TOILET TRAINING PADA ANAK DI PAUD HARAPAN BUNGA BANGSA PALEMBANG - Arly Febrianti (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2021)
Toilet training is an effort to train children to be able to urinate and defecate on their own, toilet training is an important aspect in the development of toddler age children that must receive parental attention in urinating and defecating. Demographic characteristics related to age, education and occupation can affect a child's development and ability to perform toilet training. The aim of the study was to determine the relationship between maternal demographic characteristics and the ability of toilet training in children. The research method is cross sectional and the research sample is taken using a total sampling technique with a total of 72 respondents who have children at PAUD Harapan Bunga Bangsa Palembang. This research was conducted on January 29, 2021 using research instruments in the form of a questionnaire and a check list. The results of the study using the Chi Square test showed that there was a relationship between education (p = 0.000), knowledge (p = 0.000), occupation (p = 0.002) and toilet training abilities in children. There is no relationship between age (p = 0.579) with toilet training ability in children. Health workers are expected to provide counseling to schools about the importance of toilet training in early childhood.